THE INFLUENCE OF DISTANCE LEARNING DURING THE WAR ON THE DEVELOPMENT OF COMMUNICATIVE COMPETENCES IN MEDICAL UNIVERSITY STUDENTS. - Юрків, Оксана (SWorldJournal, 2022)
Based on the analysis of literary sources, data are presented on the formation of professional communicative competencies in students studying at medical faculties in conditions of distancing during the war. This article presents and analyzes the training